Effect of Mouthwashes for COVID-19 Prevention on Surface Changes of Resin Composites - Saijai Tanthanuch; Boonlert Kukiattrakoon; Chailuck Naiyanart; Tanyanat Promtong; Panuwit Yothinwatthanabamrung; Suttida Pumpua (Elsevier, 2023)
ABSTRACT: Objective: The aim of this research was to investigate the effect of various mouthwashes for COVID-19 prevention on surface hardness, roughness, and colour changes of bulk-fill and conventional resin composites and determine the pH and titratable acidity of mouthwashes. Methods: Four hundred eighty specimens were fabricated in cylindrical moulds (10 mm in diameter and 2 mm in thickness). Before immersion, baseline data of surface hardness, roughness, and colour values were recorded. Each product of specimens (Filtek Z350XT, Premise, Filtek One Bulk Fill Restorative, SonicFil 2) were divided into 4 groups for 0.2% povidone iodine, 1% hydrogen peroxide, 0.12% chlorhexidine, and deionised water (serving as a control). The specimens were immersed in mouthwashes for 1 minute and then stored in artificial saliva until 24 hours. This process was repeated for 14 days. After immersion, surface hardness, roughness, and colour values of specimens were measured at 7 and 14 days. The data were statistically analysed by 2-way repeated analysis of variance, Tukey honestly significant difference, and t test (P < .05). Results: After immersion, all mouthwashes caused significantly lower surface hardness and greater roughness and colour values (P < .05) on all resin composites tested. Conclusions: Mouthwashes had an effect on all resin composites evaluated leading to a significant decreased surface hardness and an increased roughness and colour values (P < .05).